math

The equation: T= 2* pi* sqrt(2/3L/9.8) Solve for L. Please show the solution step by step. The square root is giving me trouble in my solution. Thanks for your help.

  1. 👍 0
  2. 👎 0
  3. 👁 202
asked by alice
  1. If L is known:

    1. Plug-in the value of L.

    2. Simplify the quantity under the radical.

    3. Take the square root of the number
    under the radical.

    Example:

    L = 19.6 m.
    Solve for T.

    T = 2pi*sqrt((2/3)*L/g)
    T = 6.28*sqrt((2/3)*19.6/9.8) =
    6.28*sqrt((2/3)*2) = 6.28*sqrt((4/3) =
    6.28 * 1.1547 = 7.25 s.

    Freq. = 1/T Hz.

    1. 👍 0
    2. 👎 0
    posted by Henry

Respond to this Question

First Name

Your Response

Similar Questions

  1. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine

    asked by Reggie on May 20, 2007
  2. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

    asked by Anonymous on October 25, 2018
  3. PreCalc

    Approximate the solutions to the following equation on the interval [0,2π). Round your answer to four decimal places. sinθ=0.65 Apparently, there suppose to be two answers to this question with a comma separating​ both

    asked by chizoba on August 15, 2016
  4. Math

    I need help solving the problem not the answer. (Multiple Choice) The steps below show the incomplete solution to find the value of x for the equation 7x + 8 − 3x = −6 + 10: Step 1: 7x + 8 − 3x = −6 + 10 Step 2: 7x + 8 −

    asked by Ryan on March 30, 2017
  5. Math (Check 2 answers please)

    1. What is the value of b in the equation b + 8 = 13? A. 5**** B. 8 C. 13 D. 21 2. The steps below show the incomplete solution to find the value of x for the equation 7x − 3x − 4 = −1 + 21: Step 1: 7x − 3x − 4 = −1 +

    asked by Alex on March 30, 2017
  6. math/algebra

    solve each of the following systems by substitution. 16) 5x -2y = -5 y - 5x = 3 20) 8x -4y = 16 y = 2x - 4 28) 4x -12y = 5 -x + 3y = -1 Step one: Solve on of the equations for one of the variables. y=2x-4 Step two:Substitute the

    asked by Diana on June 7, 2007
  7. algebra

    Can someone please show me how to solve this problem step by step thanks an advance sqrt 7x sqrt 21y multiply then if possible simply by factoring

    asked by Anonymous on February 29, 2012
  8. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

    asked by Valerie on October 22, 2019
  9. math,help,algebra I

    I need help can someone help me get unstuck and let me know if i am correct.thank you. solve by completing the square. 4x^2+2x-3=0 this is what i am doing: i used the quadratic equation. so where i am is in this step: x = (-2 (+-)

    asked by jasmine20 on April 14, 2007
  10. Pre-Algebra [urgent!]

    I can't find the solution to this problem; can someone please show me how to solve it step-by-step? Solve the equation for y in terms of x: 1. -8x + 5y = 10 Thanks! -MC

    asked by mysterychicken on May 4, 2009

More Similar Questions